Impact of prior treatment on feasibility and outcomes of Zenker’s peroral endoscopic myotomy (Z-POEM) - Sanaei, Omid; Ichkhanian, Yervant; Mondragón, Oscar V. Hernández; Nieto, Jose; Krishnan, Arunkumar; Tantau, Marcel; Tantau, Alina; Desai, Pankaj N.; Ginsberg, Gregory G.; Saumoy, Monica; Deshmukh, Ameya; Attaar, Mikhail; Farha, Jad; Jovani, Manol; Al-Ghamdi, Sarah S.; Ujiki, Michael; Khashab, Mouen A. (Endoscopy, 2020)
Background Zenker’s peroral endoscopic myotomy (Z-POEM) is a novel procedure for the management of symptomatic Zenker’s diverticulum. This study aims to report the technical feasibility and outcomes of Z-POEM in the management of Zenker’s diverticulum after prior failed interventions. Methods Patients with persistent or recurrent symptoms after prior endoscopic and/or surgical intervention for Zenker’s diverticulum were retrospectively included. The primary outcome was clinical success, defined as complete or near complete resolution of dysphagia (dysphagia score of 0 or 1) without the need for repeat endoscopic or surgical intervention during follow-up.Results Z-POEM was technically successful in 30/32 patients (93.8 %). Clinical success was achieved in 29/30 patients (96.7 %), and Z-POEM significantly reduced the median (interquartile range [IQR]) dysphagia score of patients from 2 (1 – 2) to 0 (0) (P < 0.001) over a median duration of follow up of 166 days (IQR 39 – 566). Four patients (12.5 %) had adverse events (two inadvertent mucosotomies and two leaks found on post-procedural esophagrams). Conclusion Z-POEM is feasible, safe, and effective in the majority of patients with recurrent symptoms after prior surgical or endoscopic interventions.